2013
DOI: 10.11648/j.ajaa.20130104.11
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for Charged Polytropic Stars with Van Der Waals Modified Equation of State

Abstract: We extend the work of Mafa Takisa and Maharaj (2013) by considering Van der Waals modified equation of state with polytropic exponent for anisotropic matter distribution in the study of a compact relativistic objects. New exact solutions for Einstein-Maxwell equations are generated in terms of elementary functions. The behaviour of physical variables as energy density, charge density and radial pressure is consistent with seminal treatments which suggest relevance in the description of relativistic compact sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Based on a particular form of the anisotropy factor, a class of exact solutions of Einsteins gravitational field equations describing spherically symmetric and static anisotropic stellar type configurations was obtained by Mak and Harko [8]. A variety of simple models for strange stars was constructed and compared by Avellar and Horvath [12]. Bini et al [12] studied the perturbation of white dwarf by using the 'effective geometry' formalism which was described as a self-gravitating fermion gas with completely degenerate relativistic EoS of barotropic type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a particular form of the anisotropy factor, a class of exact solutions of Einsteins gravitational field equations describing spherically symmetric and static anisotropic stellar type configurations was obtained by Mak and Harko [8]. A variety of simple models for strange stars was constructed and compared by Avellar and Horvath [12]. Bini et al [12] studied the perturbation of white dwarf by using the 'effective geometry' formalism which was described as a self-gravitating fermion gas with completely degenerate relativistic EoS of barotropic type.…”
mentioning
confidence: 99%
“…A variety of simple models for strange stars was constructed and compared by Avellar and Horvath [12]. Bini et al [12] studied the perturbation of white dwarf by using the 'effective geometry' formalism which was described as a self-gravitating fermion gas with completely degenerate relativistic EoS of barotropic type. Pagliara et al [12] studied the hydrodynamic simulation under the hypothesis that the conversion of a hadronic neutron star into a strange star is a combustion process and they also calculated the neutrino signal which is expected when a neutron star, decay into a strange quark star.…”
mentioning
confidence: 99%
“…In agreement with Feroze and Siddiqui [18] and Malaver [34], is chosen the form of the gravitational potential, ( )…”
Section: Classes Of Modelsmentioning
confidence: 99%
“…Thirukkanesh and Ragel [25] have obtained particular models of anisotropic fluids with polytropic equation of state which are consistent with the reported experimental observations. Malaver [26,27] [30,31] have studied extensively the behavior of static spherically symmetric relativistic objects with anisotropic matter distribution considering the Tolman VII space-time. Pant et al [32] have found new exact solutions of the field equations for anisotropic neutral fluid in isotropic coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this has been proved to be very useful to explore characteristics of relativistic compact objects [8,9,10,11,12,13,14,15]. In recent years, many exact solutions to the Einstein field equations have been generated by different approaches [16,17,18,19,20,21,22]. Therefore, the Einstein-Maxwell spacetime geometry for a compact object having local anisotropic effect has attracted considerable attention in various physical investigations.…”
mentioning
confidence: 99%